2012
DOI: 10.1007/s10867-012-9283-7
|View full text |Cite
|
Sign up to set email alerts
|

Nano breathers and molecular dynamics simulations in hydrogen-bonded chains

Abstract: Non-linear localization phenomena in biological lattices have attracted a steadily growing interest and their existence has been predicted in a wide range of physical settings. We investigate the non-linear proton dynamics of a hydrogen-bonded chain in a semiclassical limit using the coherent state method combined with a Holstein-Primakoff bosonic representation. We demonstrate that even a weak inherent discreteness in the hydrogenbonded (HB) chain may drastically modify the dynamics of the non-linear system, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Indeed, the investigations of localization modes in lattices with graded mass and graded interaction have obtained the equivalent results, which then supports our noting here [22]. Besides, we would like to mention that the alternating lattice is also associated with some real systems, such as the hydrogen-bonded chains with alternating intraand intermolecular covalent bonding interactions [23], the alternating bond Ising chains (having a nonuniversal critical dynamics by introducing the bonds alternating) [24], and the supperlattices (can be viewed as chains with regularly varying exchange interactions) [25]. In particular, it can model the carbon nanotubes with bond length alternation, since the bond force constant depends on the length.…”
Section: Introductionsupporting
confidence: 87%
“…Indeed, the investigations of localization modes in lattices with graded mass and graded interaction have obtained the equivalent results, which then supports our noting here [22]. Besides, we would like to mention that the alternating lattice is also associated with some real systems, such as the hydrogen-bonded chains with alternating intraand intermolecular covalent bonding interactions [23], the alternating bond Ising chains (having a nonuniversal critical dynamics by introducing the bonds alternating) [24], and the supperlattices (can be viewed as chains with regularly varying exchange interactions) [25]. In particular, it can model the carbon nanotubes with bond length alternation, since the bond force constant depends on the length.…”
Section: Introductionsupporting
confidence: 87%
“…This effect is well‐known for the nonlinear lattices . It has been observed in one‐dimensional , two‐dimensional (), and three‐dimensional () models. This phenomenon is interesting because the unstable dynamics can be highly nontrivial and counterintuitive.…”
Section: Modulational Instability and Discrete Breathersmentioning
confidence: 73%
“…Kavitha et al also reported the solitonic dynamics of the chain polarization in HB systems, when tunnel processes prevail over the thermal activation and analyzed the tunneling between two opposite directions governed by a bistable potential system at low temperature [2,5]. They suggested a possible coherent tunneling mechanism of spontaneous polarization oscillations of HB chain.…”
Section: B(x T)mentioning
confidence: 99%
“…For this reason, peptides have served as valuable models for larger biomolecules and proteins. A special property of PGs is their ability to form HBs [2] with each other, and with water and other molecules in the environment. The study of HB chains [3][4][5] can lead to insight regarding how local interactions can dictate global features of PCs and proteins.…”
Section: Introductionmentioning
confidence: 99%